Epstein-Barr Virus Versus Novel Coronavirus-Induced Hemophagocytic Lymphohistocytosis: The Uncharted Waters - Rawan Amir MD; Asim Kichloo MD; Jagmeet Singh MD; Ravinder Bhanot MD; Michael Aljadah MD; Akshay Kumar MD; Michael Stanley Albosta MD; Shantanu Solanki MD, MPH (SAGE Publishing, 2020)
Hemophagocytic lymphohistocytosis (HLH) is a hyperinflammatory syndrome characterized by fever, hepatosplenomegaly, and pancytopenia. It may be associated with genetic mutations or viral/bacterial infections, most commonly Epstein-Barr virus (EBV) and cytomegalovirus. As for the novel coronavirus, severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), also known as COVID-19 (coronavirus disease-2019), the cytokine storm it triggers can theoretically lead to syndromes similar to HLH. In this article, we report a case of a 28-year-old female who presented with high-grade fevers, found to have both SARS-CoV-2 and EBV infections, and eventually began to show signs of early HLH. To our knowledge, this is the first case reported in literature that raises the possibility of SARS-CoV-2-related HLH development.